The Grief Beneath Your Mothertongue: Listening Through Poetic Inquiry (LEARNing Landscapes, 2010)
This paper examines the process of writing a first poetry collection, A Hat to Stop a Train, as an example of poetic inquiry that has taught, and continues to teach about listening in and through language. It explores language as mothertongue, beginning with our relationships with our mothers and entwined with developing a poetic voice. Poetic inquiry brings insights into issues of silence and voice, loss and grief, for the author and her own writing, and also for the adult literacy learners she works with, whose circumstances and cultural and linguistic dislocations require careful listening.
Keywords: poetry; poetic inquiry; language; mothertongue; poetic voice; voice; silence; adult; listening